Organization of Teaching Economics at the University - Yorbekova Dilorom Muxammadkulovna; Raximova Umida Rabbimovna; Narzieva Guzal Bakhtiyorovna (Periodica Journal, 2023)
Currently, an increasing number of Uzbek universities offer school graduates training in the specialty "economist". Every year, an increasing number of professions appear that are necessary for the development of society and the well-being of the country as a whole, in which knowledge of economics plays a dominant role, so it is important to introduce economics into the school curriculum so that students can make a choice in favor of the specialty "economist", and also to navigate in modern economic realities. The purpose of the article is to study the organizational and methodological process of teaching economics in universities
Keywords: universities; modern society; younger generation